Spatial Distribution Patterns of Waste Disposal Sites in the Context of Urban Environmental Services in Yogyakarta City - Kurniati, Ayu Candra; Fanani, Fahril (ReTII, 2025)
Rapid urbanization in Yogyakarta City poses serious challenges to municipal solid waste management, exacerbated by the recent regional landfill crisis. Efficiency of municipal solid waste management heavily relies on the spatial distribution of crucial infrastructure, namely Temporary Disposal Sites (TPS). This study aims to (1) map the absolute distribution of TPS and (2) analyze their spatial distribution patterns to identify service concentrations and gaps in Yogyakarta City. This research employs a quantitative approach using spatial analysis methods, specifically Kernel Density Estimation (KDE), with 45 urban villages (kelurahan) as analysis units. Data includes TPS coordinate points from the Environmental Agency and administrative data. The results show that TPS distribution is highly uneven. Kotabaru urban village has 15 units, whereas Muja Muju urban village has none. The KDE analysis confirms the pattern is highly clustered. A primary hotspot (very high density) is identified in the central-northern area (Gondokusuman and Jetis), correlating with the commercial center. Conversely, extensive coldspots (very low density) cover most residential areas in the south (Umbulharjo, Kotagede) and periphery. This finding reveals a significant spatial mismatch between service provision locations (centralized in commercial areas) and service demand locations (dense residential areas). This study concludes that a tangible service gap exists and recommends facility redistribution and prioritizing new TPS development in coldspot zones to enhance environmental service equity.